Immunohistochemical study of the plasminogen activator system in benign epithelial odontogenic lesions - Carla Samily de Oliveira Costa; Rodrigo Porpino Mafra; Larissa Santos Amaral Rolim; Lélia Batista de Souza; Leão Pereira Pinto (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract: The aim of this study was to analyze and compare the immunohistochemical expression of plasminogen activator system (PAS) proteins (uPA, uPAR, and PAI-1) in ameloblastomas (AMBs), odontogenic keratocysts (OKCs), and dental follicles (DFs) representing normal odontogenic tissue, as well as to investigate possible correlations between these proteins. Twenty AMBs, 20 OKCs, and 10 DFs were selected for immunohistochemical analysis. In each case, the immunoexpression of uPA, uPAR, and PAI-1 was evaluated semiquantitatively based on the percentage of positivity in odontogenic epithelial and connective tissue cells. The epithelial immunoexpression of uPA was significantly lower in AMBs when compared to OKCs (p = 0.001) and DFs (p = 0.029). Significantly higher epithelial immunostaining for uPAR was observed in AMBs when compared to OKCs (p < 0.001). There were no significant differences in the epithelial immunoexpression of PAI-1 between AMBs and OKCs (p = 1.000). The correlations found for the expression of the studied proteins were not statistically significant (p > 0.05). However, the epithelial and connective tissue expressions of uPAR have a strong positive and statistically significant correlation in AMBs. The present results suggest that uPA is involved in the pathogenesis of OKCs and that uPAR may participate in tumorigenesis in AMBs. The high percentage of PAI-1-positive cells suggests a possible role for this protein in the development of AMBs and OKCs. Furthermore, the studied proteins do not seem to act synergistically in AMBs, OKCs, and DFs.